Privatization and Firm Performance: An Empirical Study of Selected Privatized Firms in Nigeria - Abdullahi, Yahya Zakari; Abdullahi, Hussainatu; Mohammed, Yelwa (Mediterranean Journal of Social Sciences, 2012)
The aim of this study is to investigate the financial and operational efficiency of the privatized firms in Nigeria. Data forthis study comes from secondary sources; specifically, Fact Book from the Nigerian Stock Exchange, Offer Prospectuses, aswell as published annual reports and financial statements of the privatized firms. Our sampled firms are drawn frommanufacturing, oil marketing, banking and insurance sub-sectors of the Nigerian economy. The period of analysis covers 5 yearsbefore, and 5 years after privatization. To test our predictions, we follow the techniques of Megginson et al. (1994) in order todetermine post privatization performance changes. We calculate the mean value of each variable for each firm over the pre andpost privatization periods, we then use the T- test and the Wilcoxon sign rank test as principal methods of testing for significantchanges in the variables. Results obtained from this study are mixed. Whereas some companies in our sample showimprovements in some indicators, other companies have shown decline in some indicators after privatization. However, in spitethe mixed results, the overall picture shows improvement in profitability for at least half of the firms in our sample. Overall, wemay conclude that our results provide little evidence that privatization has caused significant improvement by all indicators.